(3NeQI HGHd hZfGA GdHdGHds - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s ((3YHO GdLdjd Hf MVQI GdeDda s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Ydi ceGdg CeG HYO ajbhd GdabjQ YHO GdZfi Hf ESeGYjd gPG GdPi bO fGhdJg jO Gdghi cHOG HgG ChOJ ecGHOI Gdfhi s
(3BNQgG (B:s
(3dGJbd di ef ge age ai GdJLdi Ef ageJge ge GdLHGd GdQhGSi hGdMeO ddg ChdkG hBNQkG hXGgQkG hHGWfkG hgPG BNQ GdOjhGf Gdejehf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs